Personal identification number entry for Google glass. (October 2017) - Seo, Hwajeong; Kim, Jiye; Kim, Howon; Liu, Zhe
Highlights: Secure PIN-entry method against Shoulder-surfing attack with Google glass. Implementation of prototype products for proposed PIN-entry method. Masked password transmission techniques for Google glass. Graphical abstract: Abstract: In this paper, we introduce secure and efficient Personal Identification Number (PIN)-entry technologies for representative Augmented Reality (AR) devices (e.g. Google glass). The AR device supports an overlay screen, which displays the AR images and information. Since the overlay screen is only practically visible to the device holders, the screen can be used to deliver the secret parameters without loss of information. By taking advantages of the new secure medium, we present PIN-entry technologies for AR devices. In the method, we display a password layout consisting of random numbers on the screen. The users correct the input password through the voice or touch gesture. When the password input layout is properly corrected, the users enter the current input password. To evaluate the proposed methods, we implemented the prototype products and tested their performances in terms of usability and security. The novel methods achieved high security levels against shoulder-surfing attacks together with practically high usability.